The Escape from Everyday Life: Wandering and Affectivity in La habitación alemana, by Carla Maliandi (Anclajes, 2024)
Centered on an Argentine woman’s wanderings through Heidelberg after an impulsive trip, La habitación alemana (2017), by Argentine writer Carla Maliandi, depicts aimless movement both as a journey of deterritorialization from the familiar, and as an investigative and tentative shift toward the experiences of a childhood marked by exile. On the one hand, wandering can be read as a movement that lies between the concepts of smooth space and striated space, as proposed by Deleuze and Guattari. On the other hand, wandering is a type of movement that can be understood as a force that connects with the vibrant nature of the environment, thus creating an affective landscape characterized by nostalgia. In line with the lack of direction in these journeys, nostalgia implies not only a return to the past but, primarily, an impulse toward a future of possibilities that questions spatiotemporal categories.
Keywords: Carla Maliandi; Mobility; Everyday Life; XXI century; Latin American Literature